Pengaruh Harga, Kualitas Produk, dan Promosi terhadap Keputusan Pembelian Produk Fasion di Marketplace Shopee: Studi Kasus: Mahasiswa di STIE Dharma Putra Semarang - Imam Agus Kurniawan; Ida Martini Alriani (Jurnal Transformasi Bisnis Digital, 2026)
This study aims to analyze the influence of price, product quality, and promotion on purchasing decisions of fashion products on the Shopee marketplace (Case Study: Students of STIE Dharma Putra Semarang). Data were collected using a questionnaire, with respondents selected through purposive sampling. The sample consisted of 50 students from STIE Dharma Putra Semarang who had previously purchased fashion products on Shopee. Based on hypothesis testing, the first hypothesis shows that price has a positive and significant effect on purchasing decisions (t = 2.638 > t-table = 1.678; regression coefficient β₁ = 0.252; significance = 0.011 < α = 0.05). The second hypothesis indicates that product quality has a positive and significant effect on purchasing decisions (t = 4.233 > t-table = 1.678; regression coefficient β₂ = 0.434; significance = 0.001 < α = 0.05). The third hypothesis reveals that promotion has a positive and significant effect on purchasing decisions (t = 3.924 > t-table = 1.678; regression coefficient β₃ = 0.341; significance = 0.001 < α = 0.05). Therefore, it can be concluded that the more competitive the price, the better the product quality, and the more attractive the promotions offered, the higher the purchasing decision for fashion products among students on the Shopee marketplace.